Event-triggered output feedback control for discrete Markov jump systems under deception attack. Issue 11 (July 2020) - Gao, Jinfeng; Zhao, Zhen; Wang, Jinxia; Tan, Tian; Ma, Miao
Abstract: An event-triggered dynamic output feedback control (DOFC) problem for discrete Markov jump systems is considered, where both measurement and control channel are under the deception attacks. To reduce the data traffic in the channel and the control actions against attack, two event-triggered schemes (ETSs) are implemented on sensor and controller node asynchronously. And two quantizers are installed independently. Sufficient criterions for ensuring asymptotic stability of the networked control systems (NCSs) are obtained by deriving the Lyapunov functional, and the co-design of DOFC with ETSs can be acquired in terms of the linear matrix inequality (LMI). An application on DC motor is utilized to prove the feasibility of this method.